Aplikasi Augmented Reality pada Sistem Informasi Smart Building - Zahir Zainuddin; Intan Sari Areni; Raden Wirawan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
The aim of this research in this paper is to develop smart building information application using augmented reality in android mobile gadget. A case study is implemented in STMIK Handayani Makassar. The system is able to show the room condition, temperature, and humidity with marker based tracking. Performance evaluation is done with marker testing, with distance, angle, and blocked marker surface area as parameters. The result shows that the best distance between the gadget and marker is 10 cm - 50 cm with mobile angle 00 – 300 and coveraged surface area 10% - 70%. Specifications of the device are 1 GB RAM, 5 MP Camera, Android 4.4 OS, and Quad core 1 GHz Processor.